Vocabulary Explanations and Second Language Development in Adult Beginning-Level ESOL Classroom Interaction: A Conversation Analysis Perspective - Tai, K (2018)
A small body of recent research on vocabulary explanations (VEs) in second language (L2) classrooms (e.g. Mortensen, 2011; Waring et al., 2013) has attempted to provide the sequential descriptions of the key elements of VEs and investigate how teachers draw on their linguistic and semiotic resources to construct the VE sequences (e.g. Smotrova and Lantolf, 2013). Nevertheless, more work is needed in order to allow educators to better understand how VEs are provided in L2 classrooms. In particular, there is a shortage of studies (e.g. Tai and Brandt, 2018) illustrating the nature of VEs in beginning-level English for Speakers of Other Languages (ESOL) classrooms, where learners all share different first languages (L1s) and have limited English proficiency. Moreover, the shared linguistic resources between the teacher and learners are typically limited in beginning-level ESOL classrooms. To date, there is no longitudinal study which will allow for tracking the impact of VEs on contributing to learners' conceptual understandings of the meanings of target vocabulary items. The vast majority of the studies, which identified learners' display of understanding of L2 word meanings in classroom interactions, were based on one-off analyses of the classroom discourse (e.g. Waring et al., 2013). This prevents educators and researchers from observing the learner's change of conceptual understandings over time. This MSc dissertation contributes to the identified research gaps by employing Conversation Analysis (CA) to 1) investigate the nature of VEs in a beginning-level ESOL classroom and 2) conduct a 4-month longitudinal analysis to explore the potential for employing CA as the methodological tool for tracking learners' development of the conceptual understandings of the meanings of particular vocabulary items which are previously explained. The classroom data is taken from a corpus of video-data collected in a beginning-level adult ESOL classroom in the United States. The key findings demonstrate that other than verbal 3 resources, teacher's use of embodied resources in explaining vocabulary items in the classroom plays an important role in facilitating the learners' understandings of the meanings of different vocabulary items. The learner's use of gestures allows her to externalise her understandings of the L2 word meanings and also allows teachers to evaluate the learner's current knowledge states. These findings also suggest that CA provides some, albeit incomplete, evidence of the learner's developing conceptual understandings of L2 word meanings and it allows researchers to investigate how these developmental changes occur in each interactional context of L2 vocabulary use.